Structural Analysis of Tobacco Etch Potyvirus HC-Pro Oligomers Involved in Aphid Transmission - Ruiz-Ferrer, Virginia (American Society for Microbiology, 2005)
Oligomeric forms of the HC-Pro protein of the tobacco etch potyvirus (TEV) have been analyzed by analytical ultracentrifugation and single-particle electron microscopy combined with three-dimensional (3D) reconstruction. Highly purified HC-Pro protein was obtained from plants infected with TEV by using a modified version of the virus that incorporates a histidine tag at the HC-Pro N terminus (hisHC-Pro). The purified protein retained a high biological activity in solution when tested for aphid transmission. Sedimentation equilibrium showed that the hisHC-Pro preparations were heterogenous in size. Sedimentation velocity confirmed the previous observation and revealed that the active protein solution contained several sedimenting species compatible with dimers, tetramers, hexamers, and octamers of the protein. Electron microscopy fields of purified protein showed particles of different sizes and shapes. The reconstructed 3D structures suggested that the observed particles could correspond to dimeric, tetrameric, and hexameric forms of the protein. A model of the interactions required for oligomerization of the HC-Pro of potyviruses is proposed.